Rational Expressions Division is the same as the division of Fractions. While dividing a Fraction you will just flip and multiply. Simply change the dividing by a fraction to multiplying by that fractionâ€™s reciprocal. Get to know the Rational Expressions Involving Division Step by Step Procedure. We even jotted a few examples onÂ Rational NumbersÂ Division explaining everything in detail.

## Procedure for Dividing Rational Expressions

The Rational Expressions Division is similar to Fractions Division. The step by step procedure is listed as under

- You just need to flip and multiply just like Fractions during the division operation.
- Later to simplify the multiplication factor the numerators and denominators.
- Later check for any duplicate factors and cancel out them.

### Solved Examples on Dividing Rational Expressions

1. Divide 3/7 by 9/45?

**Solution:Â **

= 3/7 Ã· 9/45

= 3/7*45/9

= 3*45/7*9

= 135/63

2. Simplify 3x^{4}/4Ã·9x/2?

**Solution:Â **

= 3x^{4}/4Ã·9x/2

= (3x^{4}/4)*(2/9x)

= (3.x.x^{3}/4)*(2/9x)

Canceling out the common term x we get the Rational Expression as follows

= (3x^{3}/4)*(2/9)

= (3x^{3}*2)/4*9

= 6x^{3}/36

= x^{3}/6

3. Divide and Simplify the Result (x+4)/(x^{2}-16)Ã·(x-1)/(x^{2}-4x+3)?

**Solution:**

Given Rational Expression = (x+4)/(x^{2}-16)Ã·(x-1)/(x^{2}-4x+3)

((x+4)/(x^{2}-16))*((x^{2}-4x+3)/(x-1))

Factoring out the numerators and denominators we have

= (x+4)/(x+4)(x-4)*(x-3)(x-1)/(x-1)

Canceling out the duplicate factors we get

= 1/(x-4)*(x-3)/1

= 1*(x-3)/(x-4)*1

= (x-3)/(x-4)